A study of nonlinear pedagogical teaching models for cognitive and affective development of elementary school students - Yuliarto, Hari (Jurnal Penelitian dan Evaluasi Pendidikan, 2024)
This research aims to advance the psychomotor, cognitive, and affective abilities of elementary school students through a nonlinear pedagogical approach. The method adopted is research and development which combines quantitative and qualitative analysis. From a total of 2,411 elementary school teachers in 150 elementary schools spread across the Kota District area, 52 teachers were selected as the sample in this study. Data analysis uses a quantitative descriptive approach, with a focus on the use of percentages. The results show teachers' understanding of nonlinear pedagogy with a general average score of 2.705, indicating relatively good performance. However, the lowest rating was found in the item "Teachers' Understanding of the LED Approach", with an average score of 3.247, while understanding of "Cooperative Learning" achieved the highest score, namely 4.325, indicating very good understanding. These findings reveal that overall, teachers' understanding of nonlinear pedagogy is still not optimal, underscoring the need for more in-depth training for physical education teachers, as well as strategies for effective implementation of nonlinear pedagogy in elementary schools. This research invites new initiatives for teachers to embrace and implement innovative learning strategies that suit the demands of 21st-century education while exploring the impact of nonlinear pedagogy on the learning process.